Acoustical planning for workplace health and well-being: A case study in four open-plan offices. Issue 3 (September 2019) - Lee, Young; Aletta, Francesco
Noise is the most frequent reason for complaints about environmental conditions in the workplace. It is associated with individual health and well-being and decreased productivity and performance. This study identified a set of acoustic strategies for open-plan workplaces and examined a case study applying those to four open-plan offices in the United States. The set of measures was defined based on a literature review and a focus group interview with 17 experts. A total of four topics were identified as key performance indicators of proper acoustic environments in the open-plan workplaces. A total of 19 items were then developed within these 4 topics as the protocols for planning acoustic strategies for workplace health and well-being. In the case study, the level of acoustic performance for workplace health and well-being was highest in the Dallas office (27.5 points out of a total of potential 40.0) followed by the Minneapolis office (26.0). Both offices outperformed the other offices in achieving space planning principles to control noises and occupant noise control in open spaces for acoustical privacy. A further examination on the relationships between acoustic strategies and other health and well-being key performance indicators in these offices suggests that guidance to increase occupants' auditory comfort, well-being, and performance should be sought by designers in a holistic and integrative way.